2008
DOI: 10.1051/0004-6361:200811173
|View full text |Cite
|
Sign up to set email alerts
|

A dense disk of dust around the born-again Sakurai's object

Abstract: Context. In 1996, Sakurai's object (V4334 Sgr) suddenly brightened in the center of a faint Planetary Nebula (PN). This very rare event was interpreted as being the reignition of a hot white dwarf that caused a rapid evolution back to the cool giant phase. From 1998 on, a copious amount of dust has formed continuously, screening out the star that remained embedded in this expanding high opticaldepth envelope. Aims. We present observations that we use to study the morphology of the circumstellar dust to investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 30 publications
7
51
1
Order By: Relevance
“…The emission lines, on the other hand, would derive from photoexcitation by stellar radiation of the molecules located in the material above and below the plane. This configuration is also observed for the Sakurai object (Hinkle & Joyce 2014;Chesneau et al 2009), another object thought to have suffered a very late final helium flash. Noteworthy, strong abundance similarities between Sakurai object and V854 Cen sources were detected (Asplund et al 1998).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The emission lines, on the other hand, would derive from photoexcitation by stellar radiation of the molecules located in the material above and below the plane. This configuration is also observed for the Sakurai object (Hinkle & Joyce 2014;Chesneau et al 2009), another object thought to have suffered a very late final helium flash. Noteworthy, strong abundance similarities between Sakurai object and V854 Cen sources were detected (Asplund et al 1998).…”
Section: Discussionsupporting
confidence: 61%
“…With the advent of optical interferometry, many dusty environments around evolved stars were resolved Chesneau et al 2009). Some first attempts to monitor the dust production of the RCB RY Sgr at high spatial resolution were performed with the MIDI/VLTI instrument (Leão et al 2007).…”
Section: V854mentioning
confidence: 99%
“…Thus, the contribution of born-again AGB stars to the dust reservoir in the early solar system remains unclear. However, it is noteworthy that although more than 10% of low-and intermediate-mass stars that go through a planetary nebula phase will become born-again AGB stars based on theoretical estimates (Iben et al 1996), the observed amount of C-rich dust produced by Sakurai's object (6×10 −5 M ¤ , Chesneau, et al 2009) is generally substantially lower than the amounts of C-rich dust (10 −4 −10 −2 M ¤ ) produced by lowmass AGB carbon stars (e.g., Zhukovska & Henning, 2013).…”
Section: Potential Stellar Origin(s) Of Ab2 Grainsmentioning
confidence: 99%
“…This is supported by observations of excess momenta in almost all post‐AGB outflows relative to what isotropic radiation pressure can provide (Bujarrabal et al 2001). Additionally, close companions have been detected in or around giants, bipolar post‐AGB and PNe systems and in some cases seem to be responsible for outflow shaping (Silvotti et al 2007; De Marco, Hillwig & Smith 2008; Sato et al 2008a,b; Chesneau et al 2009; Miszalski et al 2009a,b; Niedzielski et al 2009; Witt et al 2009). In particular, the recent detection of a WD with an orbiting ∼50 M J brown dwarf in a ∼2 h orbit demonstrates that low‐mass companions can survive a common envelope phase (CEP) (Maxted et al 2006).…”
Section: Introductionmentioning
confidence: 99%